An inverse problem of a differential equation in a Banach space - Maksimov, Vyacheslav I. (Zielona Góra: Uniwersytet Zielonogórski)
A problem of dynamical reconstruction of the unknown right hand side for a linear differential equation in a Banach space is considered. A numerical solution method based on certain constructions of the theory of positional (closed-loop) control and modelling is suggested.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka